Penggunaan Model Pembelajaran Student Centered Learning (SCL) Pada Mata Kuliah Kimia Bahan Alam - Lili Andriyani (Jurnal Konseling dan Pendidikan, 2018)
The learning process that implements the lecturers as the only source of knowledge, it turns out that in fact gives rise to a variety of polemics in the education field, including  not motivation  students to study more enterprising and find other resources relevant to the field of  science. Natural Products Chemistry course is the course that are associated with the natural surroundings, so it takes a model of learning which increase the curiosity of the students will be the condition of the environment. The application of the model of Student Centered Learning (SCL) is one model that could be applied in learning so that an increase in the motivation to learn.